Employee Engagement as a Mediator Between Leadership Competence and Change Management: A Conceptual Framework for Saudi Healthcare Transformation - Aljohani, Rayhanah Sulaiman; Abdulsamad, Akram (Advances in Social Sciences Research Journal, 2026)
Healthcare transformation under Saudi Arabia’s Vision 2030 has heightened the need for competent leadership capable of guiding complex organizational change within newly established healthcare clusters. Despite recognition of leadership’s central role in reform implementation, limited research has examined the mechanisms through which leadership competence influences change management outcomes in healthcare settings. This conceptual study develops an integrated framework linking leadership competence, employee engagement, and change management within the Madinah healthcare cluster. Grounded in transformational leadership theory and social exchange theory, the proposed model positions leadership competence as a strategic capability that directly enhances management effectiveness and indirectly influences change outcomes through employee engagement. Employee engagement is conceptualized as a mediating mechanism that translates leadership competence into employees’ psychological investment, adaptability, and change-supportive behaviors. By shifting from direct-effect assumptions toward a process-oriented explanation, the framework advances leadership and organizational change scholarship in three ways: it integrates transformational and relational theoretical perspectives; it highlights employee engagement as a central explanatory pathway; and it contextualizes leadership-driven change within Saudi healthcare reform. The study offers theoretical grounding for future empirical testing and provides practical implications for healthcare leaders and policymakers seeking sustainable transformation in high-reliability healthcare systems.